THE DIVERSITY LIVELIHOOD OF CORN FARMER HOUSEHOLDS: EVIDENCE FROM TRANSMIGRATION PROGRAM OF GORONTALO PROVINCE, INDONESIA - Murtisari, Amelia; Fitri, Ichlasia Ainul; Kurnia, Theresa Dwi (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
The corn farmer households examined in this study participated in the dryland transmigration program to enhance welfare by furnishing livelihood capital to poor farmer households. This research compares the livelihood capital of corn farmer households in the transmigration areas of Gorontalo and Boalemo districts, Gorontalo, Indonesia, and examines its impact on their livelihood strategy selection. The study involved 240 poor corn farmer households. Data analysis was conducted by computing the livelihood capital index through entropy weighting analysis, followed by multinomial logistic regression analysis to examine the influence of livelihood capital on livelihood strategies. Findings indicate a higher level of livelihood capital in Boalemo Regency than in Gorontalo Regency, with Boalemo District outperforming in physical and human capital. In contrast, the Gorontalo district excels in natural and social capital. However, the financial capital of corn farmer households in both regions still needs to be improved. Natural and human capital significantly influences the likelihood of corn farming households opting for on-farm strategies over a combination of on-farm and off-farm strategies. In the case of on-farm and off-farm strategies, natural capital substantially enhances the probability of corn farmer households selecting both on-farm and off-farm strategies rather than solely on-farm and non-farm strategies. Conversely, physical capital diminishes the likelihood of corn farmer households adopting both on-farm and off-farm strategies compared to the combination of on-farm and non-farm strategies.